KARAKTERISTIK SOSIAL EKONOMI DAN KEBIJAKAN MITIGASI KONFLIK MANUSIA-GAJAH DI RESORT BESITANG, TAMAN NASIONAL GUNUNG LEUSER (SOCIAL-ECONOMIC CHARACTERISTICS AND POLICY FOR MITIGATION HUMAN-ELEPHANT CONFLICT AT BESITANG RESORT OF GUNUNG LEUSER NATIONAL P - Wanda Kuswanda (Inovasi, 2018)
One of the remaining elephants habitat is Gunung Leuser National Park (GLNP) area, especially in the Besitang region. This study was aimed to identify the social-economic characteristics, land tenure, mapping and mitigation human-elephant conflict in Resort Besitang,GNLP. Data collection methods were carried out by distributing questionnaires, interviews and Focus Group Discussion. Data analysis use frequency tables and descriptive analysis. The results showed that the potential area human-elephant conflicts at Besitang resort was identified in Halaban, Aras Senapal, Sekundur, Bukit Selamat as well as Bukit Mas Villages with low to high conflict intensity. The main cause of human-elephant conflict is fragmentation of forest area, uncertainty of land status in buffer zone, high population growth and rising migrants in Besitang region, encroachment and ilegal logging, lack of public awareness and role village institutions to participate on the elephants conservation. Policy recommendations for mitigation human-elephants conflict are 1) improving in elephants habitat fragmented at the GNLP area, 2) increase the role of Conservation Response Unit team, 3) establish rapid reaction units to handle human-elephant conflict by involving the stakeholders, 4) planting the plant species are not liked and shunned by the elephant, 5) reducing the communities agricultural systems does not require a large area, 6) to develop programs for help increase crop yields as well as 7) counseling to improve understanding that elephants are part of an ecosystem that must be protected. Keywords : elephant, conflict, habitat, Besitang, Gunung Leuser National Park.